The Communication Performance Analysis of the In Room Dining Division at Hotel “A” as the Basis for the Formation of Organizational Culture - Tham, Michael; Winarko, Hilarius Bambang (International Journal Labs, 2024)
Communication performance and organizational culture are closely related, in the process an individual's communication performance reflects their organization's culture. Every company has its organizational culture, including Hotel “A,